Genetic manipulation of folate in rice - Anukul, Nampeung (2010)
Folate malnutrition is a major problem in many countries around the world especially in Asia and Africa. Stable foods such as rice contain very low amounts of folate. White rice which is the most popular form for human consumption contains less than 80 µg folate per 100 g. Given that it forms a major part of the South East Asian diet, rice represents an important target for enhancing folate levels.